(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
This research aims to identify the level of self-concept of teachers, and to know the difference between the members of the research sample in self-concept according to the variables of sex and experience. To acheive the objectives of the research, the self-concept was used by the researcher. The researcher studied his psychometric characteristics. In order to judge the veracity of the scale, it was presented to a group of (14) specialized arbitrators in the Faculty of Education at the Universities of Tishreen and AL_Baath, In order to study its stability, it was applied to a survery sample from outside the research. The number of teachers (males and females) from the basic education stage in Lattakia was (40). The stability of the scale was calculated by the Cronbach_Alpha method, where the value of the Cronbach _Alpha coefficient of the scale was (a=o.855). After verification of validity and reliability, the scale was applied to a sample of 688 teachers, including 370 teachers (females) and 318 teachers (males). The descriptive approach was used. The research concluded that the level of self-concept in a sample of teachers in Lattakia is at the intermediate level. There is statistically significant difference between the average grade of teachers (males) and the average grade of teachers (females) on the scale of self-concept in favor of females. There is no statisticant difference between the average respondents on the self -concept scale according to experience variable. يهدف هذا البحث إلى تعرف مستوى مفهوم الذات لدى المعلمين, وتعرف الفرق بين أفراد عينة البحث في مفهوم الذات وفق متغيري الجنس والخبرة, ولتحقيق أهداف البحث تم استخدام مقياس مفهوم الذات من إعداد الباحثة. إذ قامت بدراسة خصائصه السيكومترية. وللحكم على صدق المقياس عرض على مجموعة مؤلفة من (14) محكماً مختصاً في كلية التربية بجامعتي تشرين والبعث, ولدراسة ثباته تم تطبيقه على عينة استطلاعية من خارج عينة البحث بلغ عددها (40) معلماً ومعلمة من معلمي مرحلة التعليم الأساسي (ح1) في محافظة اللاذقية. تم حساب ثبات المقياس بطريقة ألفا كرونباخ حيث بلغت قيمة معامل ألفا كرونباخ للمقياس (a=0,855). وبعد التأكد من الصدق والثبات طبق المقياس على عينة من المعلمين البالغ عددهم (688) معلماً ومعلمة, منهم (370) معلمة, و(318) معلماً. استخدم في البحث المنهج الوصفي. وانتهى البحث إلى النتائج الآتية: يقع مستوى مفهوم الذات لدى عينة من المعلمين في محافظة اللاذقية في المستوى المتوسط, كما يوجد فرق دال إحصائياً بين متوسط درجات المعلمين ومتوسط درجات المعلمات على مقياس مفهوم الذات لصالح المعلمات, لا يوجد فرق دال إحصائياً بين متوسط استجابات أفراد العينة على مقياس مفهوم الذات وفق متغير الخبرة.